Diabetes Mellitus Foot Exercise Increase ABI (Ancle Brachial Index) Value in Type II DM Patients in The Puskesmas Cipondoh at Tangerang City - Suhanda, Parta; Kusniawati, Kusniawati; Hikmah, Ema (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
This study aims to determine the effect of diabetic foot gymnastics on the value of Ankle Brachial Index (ABI) in Type II Diabetes Mellitus patients in the Cipondoh Health Center, Tangerang City. The design used is Quasi experiment with a pre–test–post–test approach. The population of this study was 42 dm type II patients in the puskesmas work area in Tangerang city. Samples were taken using purposive sampling techniques and divided into 2 groups, 20 people in intervention groups and 22 control groups. The average ABI before diabetic foot exercises of the intervention group was 0.87 and the average ABI after diabetic foot exercises were 0.93. The results of statistical analysis showed that there was a significant difference in ABI values between the intervention and control groups after diabetic foot exercises (p-value = 0.003). It was concluded that implementing diabetic foot exercises could increase the value of ABI in type II DM patients. This study recommends that diabetic foot exercises are expected to be performed for type II DM patients and ABI examinations can be used as additional examinations, especially in DM patients who go to the Health Center.